The effect of a spontaneous induction prophage, phi458, on biofilm formation and virulence in avian pathogenic Escherichia coli - Li, Dezhi; Liang, Wei; Hu, Qingyue; Ren, Jianluan; Xue, Feng; Liu, Qing; Tang, Fang (Frontiers in Microbiology, 2022)
Prophage sequences are present in most bacterial genomes and account for up to 20%. Integration of temperate phages may have an impact on the expression of host genes, while some prophages could turn into the lytic cycle and affect bacterial host biological characteristics. We investigated the role of spontaneous induction prophages in avian pathogenic Escherichia coli (APEC), which is the causative agent of avian colibacillosis in poultry and considered a potential zoonotic bacterium related to the fact it serves as an armory of extraintestinal pathogenic Escherichia coli. We found that APEC strain DE458 had a high spontaneous induction rate in vivo and in vitro. The released phage particles, phi458, were isolated, purified, and sequenced, and the deletion mutant, DE458Δphi458, was constructed and characterized. Biofilm formation of DE458Δphi458 was strongly decreased compared to that of the wild-type strain (P < 0.01). In addition, while the addition of DNase (100 μg/mL) did not affect prophage release but could digest eDNA, it significantly reduced the biofilm production of DE458 biofilm to a level close to that of DE458Δphi458. Compared to DE458, the adhesion and invasion abilities of DE458Δphi458 increased by approximately 6-20 times (P < 0.05). The virulence of DE458Δphi458 was enhanced by approximately 10-fold in chickens based on a 50% lethal dose. Furthermore, avian infection assays showed that the bacterial loads of DE458Δphi458 in the lung and liver were increased by 16.5-fold and 10-fold (P < 0.05), respectively, compared with those of the WT strain. The qRT‒PCR revealed that deletion of phi458 led to upregulation of type I fimbriate related gene fimH and curli related gene csgC by 3-fold and 2.8-fold, respectively (P < 0.01). Our study revealed that phi458 promoted biofilm formation by spontaneously inducing and decreased virulence by repressing virulence genes.